Determinants of Agricultural Growth in Indonesia, the Philippines, and Thailand - Mundlack, Yair; Larson, Donald F.; Butzer, Rita (World Bank, Washington, D.C., 2013)
The introduction of new high-yielding varieties of cereals in the 1960s, known as the green revolution. Changed dramatically the food supply I Asia, as well as in other countries. The authors examine over an extended period, the growth consequences for agriculture in Indonesia, the Philippines, and Thailand. Despite geographic proximity, similar climate, and other shared characteristics, gains in productivity, and income differed significantly among the countries. The authors quantify these differences, and examine their determinants. They find that the new technology changed the returns to fertilizers, irrigated land, and capital, all of which proved scarce to varying degrees, Complementing technology-related changes in factor use were investments - public and private - driven in part by policy. The authors find that factor accumulation played an important role in output growth, and that accumulations from policy-driven investments in human capital, and public infrastructure, were important sources of productivity gains. They conclude that policies that ease constraints on factor markets, and promote public investment in people, and infrastructure, provide the best opportunities for agricultural growth.